Komunikasi Keluarga Urban dalam Menanamkan Nilai-Nilai Toleransi Antarumat Beragama - Reni Dyanasari; Melisa Arisanty (MediaTor (Jurnal Komunikasi), 2018)
Indonesia as a multicultural country has a problem with religious issues that trigger conflict in society. Religious is one of sensitive issue can broke the unity of Indonesia. This is a challenge for government and society to make a harmony with embedding tolerance values among religious people. Family is a medium to embedding tolerance values but it comes with various challenges to socialization the norms and values. Many families in Indonesia embedded homogenous norms and values to the family member. this homogenity  is feared to raise homogenous mindset that’s hard to accepted the diversity.  Urban families mostly has acceptance of diversity. They are do not hesitate to communicate the norms and values as a knowledge that can be understood by their family. This case is interesting to be inspected with qualitative methodology in phenomenology research strategy to get the depth of research data about family communication that used in urban family to embedding tolerance values between religious people. To the further this research will contribute to the society especially for Indonesian family to communicating about norms and values of tolerance in social life.